P-Cab Dependent Dual Therapy Versus PPI Dependent Triple Therapy Against H Pylori Infection in Acid Peptic Disease - Namra Iqbal, Hafiz Muhammad Imran Aziz, Farooq Sultan, Shehla Tabussam, Akfish Zaheer, Rabia Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: H Pylori infection is associated with multiple conditions of gastroenterology like gastritis, mucosal ulcer and dyspepsia. Due to emergence of resistance against conventional therapeutic agents, new treatment regimens have been introduced and are superior to the older one. Objective; Compare P-CAB dependent dual therapy vs PPI dependent triple therapy against H. Pylori infection Methodology: Sample size was 400 patients, segregated into P-CAB -group and PPI-group randomly. P-CAB -group was treated with 1gm amoxicillin 8 hourly and Vonoprazole 20-mg 12 hourly daily for 4 weeks. PPI-group was treated with 1-gm amoxicillin, 500-mg clarithromycin and 20-mg Lansoprazole 12 hourly daily for 4 weeks. After four weeks of therapy, stool antigen test for H Pylori was performed to confirm H Pylori eradication. Patient with negative stool antigen test for H Pylori was labeled recovered and vice versa. Collected data was analyzed using window application SPSS (statistical package of social Sciences software). p value under 0.05 was considered significant. Results: Among P-CAB -group, 89 % patients become free from H.Pylori, while 11% patients could not recover from H.Pylori infection in spite of the same treatment. Similarly 69.5% patients of PPI-group recovered and 30.5% patients could not get rid of H.Pylori infection. Conclusion: It is concluded that P-CAB dependent dual therapy is more effective than PPIs dependent triple therapy against H.Pylori infection. Keywords: Lansoprazole, Proton Pump inhibitor, Potassium-competitive acid blocker, Vonoprazan, H. Pylori infection.